Implementation of Islamic Religious Education Values in Fostering Religious Character Through Scouting Extracurricular Activities - Qonita Elok Tafrikha; Khoirul Umam (STAI Serdang Lubuk Pakam, 2026)
Religious character development cannot be achieved solely through classroom instruction but also requires learning experiences that enable students to internalize religious values in their daily lives. This study aims to analyze the implementation of Islamic Religious Education values in fostering students’ religious character through scouting extracurricular activities at SMK Islam Kunjang Kediri. The study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the principal, Islamic Religious Education teachers, scout leaders, and students. Data were analyzed through data condensation, data display, and conclusion drawing, supported by source and technique triangulation. The findings reveal that the implementation of Islamic Religious Education values was carried out through the strengthening of aqidah, habituation of worship practices, and the cultivation of akhlaq integrated into school culture and scouting activities. Scouting activities contributed to the development of discipline, responsibility, cooperation, independence, courage, simplicity, as well as social and environmental awareness. The findings confirm that the integration of Islamic Religious Education values into scouting activities is effective in strengthening students’ religious character.